Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Kelurahan Kebon Kangkung Kota Bandung - Ismayanti, Ima (Madani: Jurnal Ilmiah Multidisiplin, 2022)
Work motivation is an encouragement to do a job. Work motivation is closely related to one's performance. Based on this, this study aims to determine the effect of work motivation on employee performance at the Kebon Kangkung Village Office, Bandung City. This research uses quantitative methods using descriptive research methods. Collecting data in this study using the method of direct observation, direct interviews and distribution of questionnaires. The population in this study were all employees at the Kebon Kangkung Village Office, Bandung City, namely 36 people. Sampling in this study was using saturated sampling in which all populations were sampled as many as 36 people. The statistical test used in this study is correlation, simple linear regression, determination test and T test with the help of SPSS. Based on the results of the calculation of the correlation test, it can be seen that the correlation value is 0.742, which means the level of strength of the relationship between work motivation and employee performance has a strong relationship. Calculation of the coefficient of determination, it is known that the coefficient of determination is 55%, which means that the Work Motivation variable contributes 55% to the Employee Performance Variable. While the remaining 45% is caused by other factors not examined in this study. The results of the t test show the value for variable X (Work Motivation), namely t count (6.449) > t table (2.035) and sig 0.000 <? (0.005) meaning that in this study the variable X (Work Motivation) affects variable Y (Employee Performance) ). This shows that the hypothesis is accepted, namely "there is an influence of work motivation on employee performance at the Kebon Kangkung Village Office, Bandung City".